Pengaruh Disiplin Kerja, Kesehatan Kerja, dan Keselamatan Kerja Terhadap Produktivitas Karyawan PT. Machine Control & Automation - Fahmi Ramadhan; Hamdan (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The increasingly modern business world like today is very much about its development, foreign and domestic competition makes companies want to continue to increase productivity. This study aims to determine the influence of work discipline, occupational health, and occupational safety on employee work productivity at PT. Machine Control & Automation. This research is a replication study using a quantitative approach method. Sampling was taken using purposive sampling with a total sample of 84 employees. Data was obtained from the results of distributing questionnaires to respondents. This research analysis uses multiple linear regression analysis with the results of the analysis showing that work discipline, work health and work safety have an influence on employee productivity as proven by the t-test which shows tcount > ttable. The results of the F-test analysis show that work discipline, work health and work safety have a simultaneous effect on work productivity. This can be proven from the results of the f test by paying attention to the value of Fcount > Ftable. And the significance value is <0.05. The limitations of this research are employee productivity which is influenced by work discipline, work health and work safety. Suggestions for further research are expected to retest based on dimensions and indicators other than those examined in this research